CGAS – Gas Test Chamber - Pereira, Gonçalo (2020)
The tests of gas detectors, mainly toxic gas detectors, are important when a company, whose develop this type of product, wants to insure the functionality and quality of their equipment. In this sense, it is fundamental to have a system capable of performing the test autonomously, ensuring the quality and repeatability of the results. Depending on the type of gas and on the characteristics of gas detection, there are some solutions in the market but most of them are customized solutions that make the product development more expensive. The option of constructing a chamber for the testing of gas detectors is related with the fact that, on one hand test chambers with the necessary characteristics are not cost-effective and on other hand by lack of rigor and safety in the simplest chambers. So, it is intended to develop an automated standard solution that could be adapted for different type of gas detection, changing only the type of inputs – the sensors. The objective of this work is to present the development of an airtight chamber capable of performing the necessary tests to attest the correct functioning of a gas detector used in Addressable Fire Detection Systems. The test chamber prototype will be described in terms of hardware and software, as well as the tests performed for two types of gas detection, Carbon Monoxide (CO) and Liquefied Petroleum Gas (LPG). The chamber is controlled by a computer through a graphical user interface generated by LABView Software. The experimental results show that this chamber is certainly an important equipment in the preparation of gas detectors for approval in an accredited laboratory.